Association of dietary niacin intake with all-cause mortality in chronic kidney disease: A retrospective cohort study of NHANES. - Meijuan Xiang; Jianyun Peng; Zhihong Gui; Ju Jin; Jinling Meng (PLoS ONE)
Background Dietary niacin intake has a positive influence on several chronic diseases, while the impact of dietary niacin intake on prognosis in chronic kidney disease (CKD) remains unknown. The study would explore the association between dietary niacin intake and all-cause mortality in CKD patients. Methods Data about 4,659 CKD patients in this retrospective cohort study were obtained from the National Health and Nutrition Examinations Survey (NHANES). Dietary niacin intake data were acquired based on the 24-hour dietary recall interviews. Weighted univariate Cox regression models were utilized to select potential covariates. The association of dietary niacin intake with all-cause mortality was explored using weighted univariate and multivariate Cox regression models. The results were presented as hazard ratios (HRs) with 95% confidence intervals (CIs). Results In total, 4,659 CKD patients were included in the study. The mean age of patients was 58.03 (0.42) years old, and 2,502 (58.45%) were female. During a mean follow-up of 73.92 (1.14) months, 1,325 (28.44%) CKD patients died. Compared to CKD patients with lower niacin intake ≤19mg, those with niacin intake >33 mg were associated with lower all-cause mortality risk (HR = 0.79, 95%CI: 0.64-0.98). The association also found in subgroups of age ≥65 years old (HR = 0.68, 95%CI: 0.53-0.88), males (HR = 0.68, 95%CI: 0.51-0.92), BMI <25 kg/m2 (HR = 0.63, 95%CI: 0.39-0.99), smoking (HR = 0.68, 95%CI: 0.49-0.94), dyslipidemia (HR = 0.71, 95%CI: 0.56-0.91), and non-hyperphosphatemia (HR = 0.73, 95%CI: 0.58-0.91). Conclusion Adequate dietary niacin intake was related to lower odds of all-cause mortality in CKD patients. Niacin supplements may have potential benefits for prognosis in CKD patients.